LEGAL PROTECTION OF MIGRANT WORKERS AGAINST THREATS OF ABUSE DISCRIMINATION IN A DIPLOMATIC RELATIONSHIP PERSPECTIVE BETWEEN COUNTRIES - Yapiter Marpi (Faculty of Law Universitas Lampung, 2021)
Manpower is the driving force of an activity that can determine the implementation of manpower through the available manpower, which is an integral part of national development based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Problems that occur to Indonesian migrant workers abroad occur cases, abuse and discrimination occur, such as cases of sexual harassment, cases involving convictions of migrant workers, cases of unpaid wages, to cases of unilateral termination of employment. This research uses normative juridical research methods and is legally supported by socio descriptive analysis employing primary, secondary, and tertiary data. The purpose of this research is that the placement of Indonesian workers abroad is one of the State's efforts to realize the same rights and obligations for workers to improve their standard of living. The study results show that the protection of migrant workers needs to be affirmed with certainty against the regulation of Law Number 18 of 2017. The aim is to guarantee Indonesian Migrant Workers and their families in realizing guaranteed fulfillment of their rights in all activities before working, during work, and after working in legal, economic aspects, and social. The role of state diplomacy is needed in protecting and fulfilling the rights of migrant workers because this condition involves relations between countries, as people who have no choice of provider for life, workers. Therefore the role of the State must be very spearheading in providing legal protection to migrant workers because their status is minimal. The research analysis results to realize the implementation of international and national legal instruments from Indonesia need to be optimized through diplomacy from those with interest so that protection is said to be effective and optimal.